3 proofs of 2 well-known theorems on starlike and convex functions - Maslina Darus; Derek K. Thomas (Penerbit Universiti Kebangsaan Malaysia, 2022)
Let f be analytic in D = {z ∈ C : |z| < 1}, and be given by f(z) = z + P∞ n=2 anzn. We give three different proofs for the well-known sharp bounds for the second Hankel determinant |H2(2)(f)| = |a2a4 − a23 | for starlike and convex functions.